Investigating Income Effects in Scanner Data: Do Gasoline Prices Affect Grocery Purchases? - Gicheva, Dora; Hastings, Justine; Villas-Boas, Sofia (American Economic Review, 2010)
Investigating Income Effects in Scanner Data: Do Gasoline Prices Affect Grocery Purchases? by Dora Gicheva, Justine Hastings and Sofia Villas-Boas. Published in volume 100, issue 2, pages 480-84 of American Economic Review, May 2010